Human Interface And ATM Network Impairment Evaluations Of An Experimental 3D Videophone - Mohd Arif, Nor Azhar (2001)
New technologies are being developed for the next generation telecommunication systems. This is referred to as Virtual Reality Telecommunication System (VRTS). The system requires the development of new devices for sensor, processing module and actuator to enhance the accuracy and amount of information that is commonly exchangedin face-to-face communication. The concept of #D videophone is proposed to realise video communication that is much closer to natural face-to face conversation. Various system evaluations are conducted for the experimental 3D videophone set-up by adopting the subjective assessment method recommended by ITU-R. Human visual interface evaluations are conducted to confirm the display choice for the visual information presentation and the suitable terminal configuration for the system core hardware. The results show that 3D display is the preferred choice for visual information representation actuator of the 3D videophone since the representation of visual information by this display is closer to natural face-to-face conversation. On the other hand, a notebook PC is chosen as 3D videophone core hardware configuration because sufficient level of eye contact can be maintained during video communication. Evaluation of the degradation and delay of audio and 3D visual signals due to ATM network impairments is performed to verify the suitability of ATM network for handling the transmission of 3D videophone signals. The effects of the impairments are evaluated by comparison between unimpaired and impaired signals. The results demonstrate that ATM network impairments effects at the ITU-T ATM performance objective values on the signals can maintain the scale 4 of ITU-R five-grade scale. Therefore, good quality of audio and 3D visual signals transmission can be performed for ITU-T ATM performance objective. Based on the results of all evaluations conducted, the specifications of the future 3D videophone prototype are summarised.